Preparation and Photocatalytic Activity of Cu2O/Ni0.5Zn0.5Fe2O4 Microtubules - Li, Yan; Ma, Yue; Zhu, Shaofeng; Yao, Wangzhao (Asian Journal of Chemistry, 2013)
Combining the dip-calcination method, nickel-zinc ferrite (Ni0.5Zn0.5Fe2O4) microtubules were prepared using absorbent cotton as template. The Cu2O/Ni0.5Zn0.5Fe2O4 microtubules were prepared by low-temperature liquid phase method in ethanol/polyethylene glycol/H2O system of three-phase solution, which is using copper acetate and modified Ni0.5 Zn0.5 Fe2O4 microtubules as the raw materials and glucose as a reducing agent. The as-prepared samples were characterized by X-ray diffraction and scanning electron microscopy. The photocatalytic activity of the Cu2O/Ni0.5Zn0.5Fe2O4 composite microtubules was evaluated by degradation of methyl orange under ultraviolet lamp. The results show that the microtubule external diameter is between 6 and 8 μm, the wall thickness is between 0.5 and 2 μm. The Ni0.5Zn0.5Fe2O4 microtubules are composed of numerous spherical Ni0.5Zn0.5Fe2O4 nanocrystals with the nearly uniform size about 125 nm. The results also show that Cu2O/Ni0.5 Zn0.5 Fe2O4 microtubules have photocatalytic activity under the ultraviolet lamp and can be separated from the system by applying magnetic field.